Law and economics in a nutshell - Harrison, Jeffrey L. 1946- (Nutshell series, 2016)
"This guide provides expert coverage of the classic issues, including basic price theory; definitions of efficiency; the Coase Theorem; and the economics of contract law, tort law, criminal law, regulation, antitrust, and intellectual property. The text also discusses less conventional topics such as public choice, what it means to be a rational maximizer of self-interest, the assumptions underlying economic analysis as applied to law, limitations on the application of economic theory to law, the theory of second best, the prisoner's dilemma, the economics of marriage, the economics of inheritance, evolutionary theories of law, the economics of settlement, and the implications of recent research into happiness"--Publisher description